Hybrid versus catheter ablation for Hypertrophic CardioMyopathy with Atrial Fibrillation (HCM-AF): study protocol for a randomised controlled trial - Yan Yao; Zhe Zheng; Lei Song; Min Tang; Le Li; Sipeng Chen; Huiming Guo; Yajie Tang; Yumei Xue (BMJ Open)
Introduction Atrial fibrillation (AF) is an independent predictor of adverse outcomes in patients with hypertrophic cardiomyopathy (HCM). Although catheter ablation is highly recommended for general AF populations, it is less effective in maintaining sinus rhythm in patients with HCM associated with AF. Hybrid ablation, combining a cosmetic approach with a lower rate of AF relapse, lacks comparative studies to verify its efficacy against CA in HCM. This study aims to assess the rhythm control effectiveness of hybrid versus CA in non-obstructive HCM (non-oHCM) patients with AF.Methods/analysis This prospective, multicentre, randomised trial involves a blinded assessment of outcomes in non-oHCM patients with non-paroxysmal AF. Sixty-six candidates from three centres will be randomised 1:1 to either hybrid or CA, including isthmus addressed lesion sets. Participants will be stratified by left atrial (LA) size (LA diameter ≤50 mm or >50 mm). Follow-ups at the 3rd, 6th and 12th months will evaluate the primary endpoint of freedom from documented atrial tachycardia lasting over 30 s within 12 months post-procedure without antiarrhythmic drugs, along with secondary endpoints of all-cause mortality, cardiovascular-related mortality, cerebral stroke, peripheral vascular embolism, heart failure-related rehospitalisation, all-cause rehospitalisation and quality of life assessments.Ethics and disseminationapproval The central ethics committee at Fuwai Hospital has approved the Hypertrophic CardioMyopathy with Atrial Fibrillation trial (approval number: 2022-1736). Results will be disseminated through publications in peer-reviewed journals and presentations at conferences.Trial registration number NCT05610215.